Assistance in the Implementation of the Internal Quality Assurance System - Yuyun Nuriah (Publikasi Indonesia, 2024)
This study aims to map one of the internal quality assurance programs in an effort to improve the quality of schools seen from the 8 National Education Standards (SNP), the ability of school residents to carry out 5 cycles of the Internal Quality Assurance System (SPMI) at SMP Islam Cikal Harapan 01 and SMP Islam Cikal Harapan 02. Data collection techniques in this study were through questionnaires, interviews, observations, and discussions. The results showed that there was an increase in the ability to understand and implement SPMI at SMP Islam Cikal Harapan 01 and SMP Islam Cikal Harapan 02, East Jakarta. In the percentage value of quality mapping, there was an increase from 2.51% in the Pre Cycle phase to 4.21% in the first cycle phase, and the second cycle, namely quality fulfillment planning, an increase from 2.76% in the Pre Cycle phase. The results of the second cycle are quality fulfillment planning with a value of 3.87%. From the percentage value of the third cycle of quality fulfillment implementation, there was an increase from 2.4% in the pre-cycle phase to 3.2%. From the percentage value of the fourth cycle of monitoring and evaluation of the implementation of quality there was an increase from 2.7% in the pre-cycle phase to 3.8%. From the percentage value of the fifth cycle of the new quality strategy, there was an increase from 2.42% in the pre-cycle phase to 3.52%. The implication of this research for the mentoring activities carried out by the abdimas team of Unindra PGRI Jakarta is that this mentoring activity can be carried out further by involving all school members. This is needed to be able to improve the quality of education in the two schools.